2021
DOI: 10.1002/ctd2.12
|View full text |Cite
|
Sign up to set email alerts
|

Clinical standardization of metagenomic next generation sequencing (mNGS) in the pathogen diagnosis

Abstract: Background With the development and advancement of gene sequencing technologies, next generation sequencing, especially metagenomic next generation sequencing (mNGS), has been explored in infectious disease diagnosis. Aims To first introduce the standardization of each step of mNGS, the interpretation of positive and negative results and their clinic application in pathogen diagnosis. Methods A typical workflow of mNGS includes six main steps: sample collection, nucleic acid extraction, library construction, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Metagenomic next-generation sequencing (mNGS) has the potential for rapid unbiased identification of pathogens at the strain level and their corresponding antimicrobial resistance genes, which overcome the limitations of the current diagnostics methods (16). mNGS is also superior for its ability to identify microbes that are difficult to culture and detect AMR genes directly without needing a targeted assay.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metagenomic next-generation sequencing (mNGS) has the potential for rapid unbiased identification of pathogens at the strain level and their corresponding antimicrobial resistance genes, which overcome the limitations of the current diagnostics methods (16). mNGS is also superior for its ability to identify microbes that are difficult to culture and detect AMR genes directly without needing a targeted assay.…”
Section: Introductionmentioning
confidence: 99%
“…While many commercially available sequencing technologies exist, the MinION sequencer (Oxford Nanopore Technologies, UK) exhibits excellent potential for rapid point-of-care testing. This is a pocket-sized USB-connectable, portable device capable of real-time long-read sequencing and data analysis (16,17). Previous studies have shown the feasibility of using MinION to detect bacterial pathogens and antimicrobial resistance genes from urine samples (16,(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, as there is an increase in metagenomic information acquired from TFMs, the development and implementation of a metagenomic viral surveillance matrix are envisioned to outline details on viral movement between livestock and humans ( 52 ). To aid in the visualization and parsing of the vast amount of data generated from the metagenomic analysis of environmental samples, we envision the use of advanced bioinformatic pipelines capable of analyzing large data sets and producing clean and easily visualized summary reports ( 53 58 ). Importantly, the relative speed of these surveillance pipelines is only as fast as their rate-limiting step.…”
Section: Introductionmentioning
confidence: 99%